2004
DOI: 10.1097/01.ta.0000100379.54339.0e
|View full text |Cite
|
Sign up to set email alerts
|

Rinsing-Suction Reamer Attenuates Intramedullary Pressure Increase and Fat Intravasation in a Sheep Model

Abstract: Because we found only a minimal increase of the pulmonary arterial pressure as a sign of pulmonary embolism, we conclude that by using the RSR, the systemic side effects caused by intravasation of medullary content during reaming could be reduced as far as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The effect of the RIA on IM pressures was assessed in three studies [12][13][14] with a further two studies assessing a similar device, the 'rinsing-suction-reamer' (RSR) [15,16]. The RSR is cannulated and flexible allowing continuous suction and irrigation during reaming similar to the RIA; however, it has only been reportedly used in the experimental setting.…”
Section: Prevention Of Fat Embolism and Thermal Necrosismentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the RIA on IM pressures was assessed in three studies [12][13][14] with a further two studies assessing a similar device, the 'rinsing-suction-reamer' (RSR) [15,16]. The RSR is cannulated and flexible allowing continuous suction and irrigation during reaming similar to the RIA; however, it has only been reportedly used in the experimental setting.…”
Section: Prevention Of Fat Embolism and Thermal Necrosismentioning
confidence: 99%
“…The RSR is cannulated and flexible allowing continuous suction and irrigation during reaming similar to the RIA; however, it has only been reportedly used in the experimental setting. Three studies used animal models-one sheep [15] and two porcine [13,16]-with the others using human cadaver specimens [12,14]. A significant reduction in IM pressures, when the RIA/RSR was used as opposed to conventional reaming, was observed in four of five studies with an unexpected rise in distal pressures seen by Higgins et al (32.7±39.4 kPa in the RIA group compared with 17.0± 32.6 kPa in the standard reaming group; P=0.019) [12].…”
Section: Prevention Of Fat Embolism and Thermal Necrosismentioning
confidence: 99%
“…In previous in vitro investigations and animal tests, we showed that the intramedullary pressure increase and the intravasation of bone marrow content were significantly decreased. 1,2 The aim of the present study was to demonstrate whether the utilization of pressure-reduced reaming of the medullary cavity was able to reduce the systemic burden for the organism, particularly for the lung, when compared with conventional medullary reaming. This might allow expansion of the indication for reamed medullary nailing of the femur to include ''damage control orthopaedic surgery'' 3 for patients with multiple injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Husebye et al [9] reported a lower maximum intramedullary pressure reaming with the RIA (33 ± 8 mm Hg) versus using a traditional reamer (188 ± 38 mm Hg) while reaming pig femurs. Joist et al [10] used a rinsing-suction reamer for reamed intramedullary nailing in which physiologic pressure (40 mm Hg) was exceeded only during insertion of the guide wire. This rinsing-suction reamer achieved considerably lower levels of intravenous fat, as measured by Gurd criteria, compared with a standard AO reamer.…”
Section: Discussionmentioning
confidence: 99%
“…The number of fat particles observed in the lungs postoperatively correlates with increased femoral intramedullary pressure when a TKA is performed using conventional instrumentation (eg, drill, intramedullary alignment guide, and so on) [10,16]. Although the exact femoral intramedullary pressure threshold that leads to fat embolism has not been studied in humans [13], a sheep model suggests emboli (bone marrow surrounded by a thrombotic aggregate) appear at intramedullary pressures greater than 200 mm Hg [21].…”
Section: Introductionmentioning
confidence: 99%